Sustainable Livelihood of Fonae Fishermen in The Koloray Island - Abubakar, Jufri; Ndoen, Ma L. (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
Speculative haul affect the livelihood of fishermen. This uncertainty is caused by fishing in the cacth season, and fisheries resources that have open access. The subject of this study is focused on fonae fishermen in Koloray island. The aim of this reaserch is to understand the efforts of fonae fishermen to maintain sustainable livelihood in Koloray island. Using ethnographic method, this research shows that local wisdom and social capital are the efforts of fonae fishermen to maintain their sustainable livelihood. Environmentally friendly fishing gear such as fonae boat, rumpon and huhate is fisherman's wisdom to protect natural resources so that they can be utilized continuously. Meanwhile, bridging capital between fonae fishermen and linking capital between different community is to social sustainability